PENINGKATAN KUALITAS PEMBELAJARAN IPS MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE COURSE REVIEW HORAY PADA SISWA KELAS IV SD NEGERI SEKARAN 01 SEMARANG (INPROVING SOCIAL INSTRUCTIONAL QUALITY BY COOPERATIVE MODEL, COURSE REVIEW HORAY TYPE AT FOURTH SDN (Jurnal Kreatif : Jurnal Kependidikan Dasar, 2011)
Based on preliminary data obtained in SDN Sekaran 01 Semarang found the problem  about social learning studies in IV grade. Teacher does not use an innovative learning model and the activities are not centered on students learning. Students tend to be passive in the learning that results in low students activities outcomes. Therefore, there is needed for action  to improve the quality of learning social studies. One of them by using the cooperative learning model  and Course Review Horay type. Problem formulation in this research is whether the cooperative learning model and Course Review Horay type can improve  teachers skill, students activities, and students learning outcomes on improvement social studies?. This study aims to (1) teacher skill in increasing social studies learning, (2) increasing the activity of students in social studies learning, and (3) students improvement outcomes in social studies learning. The study is a classroom action research using cooperative learning model and Course Review Horay type. The study was conducted during three cycles, each cycle consisting of four stages including planning, implementation, observation and reflection. Research subjects are teacher and fourth grade students  SDN Sekaran 01 Semarang District. Data collection techniques use observation sheets, interview, test and documentation. The results of this study indicate that: the cycle of teacher skills I obtained an average score of 2.6 with good criterion. Activity students obtain an average score of 2.3 with good criterion. Learning out comes of students obtaining the average value of 66 with the percentage of 44% completeness. In cycle II, the skills of teachers increase to an average score of 3.2 with good the criteria very well. Students activity increase to an average score of 2.6 with good criterion. The results of learning increase with the average value of 71 and 67% the percentage of completeness. In cycle III the average score of skills of teachers increase to 3.8 with good the criteria very well. Average score of student activity increase to 3.5 with good the criteria very well. The average value of student learning outcomes reached 82 and the percentage reaches 93% completeness. Once action is taken on the third cycle shows that a significant increasing of teacher skill, student activities, and learning out comes on indicators and success. Therefore, through the cooperative learning model and Course Review Horay  type can improve the quality of learning. Suggestions for teacher to improve the quality of learning is needed to develop an innovative model of learning by using the cooperative learning model and Course Review Horay type. Keywords: quality of social studies learning,  cooperative model and Course Review              Horay type